On the Lattice Properties of Almost L-Weakly and Almost M-Weakly Compact Operators. (20th May 2021) - Akay, Barış; Gök, Ömer
Abstract : We establish the domination property and some lattice approximation properties for almost L-weakly and almost M-weakly compact operators. Then, we consider the linear span of positive almost L-weakly (resp., almost M-weakly) compact operators and give results about when they form a Banach lattice and have an order continuous norm.